Regulatory Developments in the Gig Economy: A Literature Review - Victory Haris Kusuma Wardhana; Maria Grace Herlina; Sugiharto Bangsawan; Michael Aaron Tuori Tuori (The Winners, 2020)
The emergence of the gig economy and its rapid growth was anticipated to play a big part in its economy. Despite the enormous benefits, the gig economy business model had also attracted numerous issues in many countries and regions. The research utilized a Systematic Literature Review (SLR) methodology by Snyder for analyzing regulation issues in the gig economy, which was divided into six steps, those were defining the central question, determining databases, using search string to find relevant keywords, extracting data, filtering data, and analyzing the findings to answer to the main question. The SLR results show licensing and misclassifications are the most dominant factors in gig economy, while regulatory issues such as safety, tax, externalities, wage, benefit, privacy, and discrimination area are other factors in it. The most popular platform types that attract regulators are work on demand, asset rental, and crowd-work.